La influencia del Departamento de Cultura, Deporte, Recreación y Turismo del Gobierno Autónomo Descentralizado Municipal de Babahoyo en el desarrollo turístico del cantón en el año 2015 - Campi Rivera, Johanna (2016)
This research is aimed at analyzing the influence of the Department of Culture, Sports, Recreation and Tourism of the Autonomous Municipal Government Decentralized Babahoyo in tourism development Canton during 2015 so by deductive methods, inductive, analytical and descriptive proceeded to execution; for this building two questionnaires that were applied to both officials working in the tourist part of the GAD and citizens of the canton was required. Given the respective analysis surveys, checking the assumptions made by the test Chi Square, where similar questions in the study population was contrasted with respect officials GAD and citizens, concluding that the Department of Culture, Sports, Recreation and Tourism Municipal GAD Babahoyo has little influence and this affects the development of tourism in Canton Babahoyo, recommending that the Municipal GAD Babahoyo proceed with the creation of the Department of Tourism to positively influence the tourism development in the canton Babahoyo. It also became clear that the Municipal GAD has a focus on long-term tourism growth, but it is short term, which is being sutured places like the beach of El Salto and the House of Olmedo and has allowed its emblems disappear as Balsa Blanca, houseboats called Balsas, Cerro Cacharí, among others, not becoming attractive to tourists.